A phase II study of vorinostat (MK‐0683) in patients with polycythaemia vera and essential thrombocythaemia. (11th June 2013) - Andersen, Christen L.; McMullin, Mary F.; Ejerblad, Elisabeth; Zweegman, Sonja; Harrison, Claire; Fernandes, Savio; Bareford, David; Knapper, Steven; Samuelsson, Jan; Löfvenberg, Eva; Linder, Olle; Andreasson, Bjørn; et al.
Summary: Inhibition of histone deacetylases may be an important target in patients with myeloproliferative neoplasms. This investigator‐initiated, non‐randomized, open‐label phase II multi‐centre study included 63 patients (19 essential thrombocythaemia, 44 polycythaemia vera) from 15 centres. The primary objective was to evaluate if vorinostat was followed by a decline in clonal myeloproliferation as defined by European Leukaemia Net. Thirty patients (48%) completed the intervention period (24 weeks of therapy). An intention‐to‐treat response rate of 35% was identified. Pruritus was resolved [19% to 0% ( P = 0·06)] and the prevalence of splenomegaly was lowered from 50% to 27% ( P = 0·03). Sixty‐five per cent of the patients experienced a decrease in JAK2 V617F allele burden ( P = 0·006). Thirty‐three patients (52% of patients) discontinued study drug before end of intervention due to adverse events (28 patients) or lack of response (5 patients). In conclusion, vorinostat showed effectiveness by normalizing elevated leucocyte and platelet counts, resolving pruritus and significantly reducing splenomegaly. However, vorinostat was associated with significant side effects resulting in a high discontinuation rate. A lower dose of vorinostat in combination with conventional and/or novel targeted therapies may be warranted in future studies.